2018
DOI: 10.1186/s12913-018-3492-0
|View full text |Cite
|
Sign up to set email alerts
|

Why are so few patients rating their physicians on German physician rating websites? A qualitative study

Abstract: BackgroundPhysician rating websites (PRWs) allow patients to rate, comment and discuss physicians’ quality online as a source of information for others searching for a physician. It is generally assumed that PRWs will only be helpful for users, and fair for the rated, if there are a high number of ratings. However, the number of ratings on PRWs remains low internationally and there is currently a lack of research examining the reasons why patients are not rating their physicians. The aim of this study is to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Similarly, a cross-sectional survey of people who had used physician rating websites in Germany found that having had a very positive or negative experience would motivate them to post feedback whereas concerns about possible negative consequences, technical issues or about site operators would stop them from doing so. 35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a cross-sectional survey of people who had used physician rating websites in Germany found that having had a very positive or negative experience would motivate them to post feedback whereas concerns about possible negative consequences, technical issues or about site operators would stop them from doing so. 35…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a cross-sectional survey of people who had used physician rating websites in Germany found that having had a very positive or negative experience would motivate them to post feedback whereas concerns about possible negative consequences, technical issues or about site operators would stop them from doing so. 35 A nationally representative survey of the US population reported that of those who had used rating sites in the preceding year, 35% said that good ratings had helped them select a physician while roughly the same proportion (37%) said that poor ratings led them to not consult the physician in question. 6 An experimental study of 500 adults recruited through a crowdsourcing website who were presented with a hypothetical review of a physician (without any other information about quality or performance) showed that predominantly negative reviews reduced the willingness of participants to consult the physician; willingness was also lower when negative reviews were presented before positive reviews.…”
Section: How Reliable Is Online Patient Feedback?mentioning
confidence: 99%
“…There is a need for a consensus-based criterion that applies to all Swiss PRWs for determining which comments are to be and not to be published publically and which are clearly publicized so users of PRWs are aware of it. Indeed, a recent qualitative study conducted with a random sample of residents of 4 North German cities reported that a lack of rating guidance in terms of allowable content was a disincentive for rating a physician on a PRW [31]. It is also likely that the removal of a comment on the whims of a PRW operator is a disincentive for users to give further physician ratings in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the fact that awareness of PRWs is an important factor, it should be noted that although the studies conducted in the United States and Germany found high awareness of the PRWs, the level of PRW usage was still found to be comparable with previous studies [3,43], suggesting that even if awareness of PRWs increases, there are other factors behind the low level of physician ratings. A recent qualitative study in Germany aiming to examine these other factors identified 2 key overarching groups of factors—first, factors concerning the physician-patient relationship and second, factors regarding the technical aspects of PRWs [44]. Although a qualitative study in 2016 with participants residing in the German-speaking part of Switzerland also highlighted the need to improve the design of PRWs, the study involved German PRWs rather than Swiss PRWs [29].…”
Section: Discussionmentioning
confidence: 99%